ON THE “SMALL” ANTOLOGY OF MACEDONIAN POETRY IN THE BOOK “WARSAW DRAWS SKOPJE” (Journal of Contemporary Philology, 2024)
The purpose of this paper is to analyze the selection of Macedonian poetry in Kinga Netman-Multanovska’s book Warsaw Draws Skopje. In addition to exceptional documentary prose, the book provides a literary topographic map of the city. 23 authors from different generations with a total of 39 selected fragments of different poems are portrayed, from authors who worked in the Kingdom of Yugoslavia, authors who show the more archaic layer of the already standardized Macedonian language, to the youngest authors. By analysing the literary topographic map of the city through the verses of the Macedonian poets, prose works and published anthological and other works, the paper aims at providing a broad view of Skopje as a theme in contemporary Macedonian literature. The analysis of Netman-Multanovska’s book shows that it is precisely the verses of Macedonian poets that contribute to building the image of Skopje as an ideal place that has managed to bring the East and the West together architecturally, as well as politically, sociologically and culturally.
Keywords: Skopje; contemporary Macedonian poetry; anthology; Kinga Netman-Multanovska; “Warsaw Draws Skopje”